Treatment with a Nucleoside Polymerase Inhibitor Reduces Shedding of Murine Norovirus in Stool to Undetectable Levels without Emergence of Drug-Resistant Variants - Rocha-Pereira, Joana (Antimicrob Agents Chemother, 2016)
Prolonged norovirus shedding may occur in certain patients, such as organ transplant recipients. We established a mouse model for persistent norovirus infection (using the mouse norovirus MNV.CR6 strain). The nucleoside viral polymerase inhibitor 2′-C-methylcytidine (2CMC), but not favipiravir (T-705), reduced viral shedding to undetectable levels. Viral rebound was observed after stopping treatment, which was again effectively controlled by treatment with 2CMC. No drug-resistant variants emerged.